(3GdeHGOF (B..(3GdfXQjI (B..(3GdJWHjbs - (3YHO GdYRjR eUWai (B, (3CHh fHYIs ((3YeGf(B:s (3OGQ GdefGgL ddfTQ hGdJhRjY(B,s, 2023)
(3jbOe cJGH (B"(3GdJShjb GdeYGUQ(B" (3fXQI TGedI Ydi YGde GdJShjb GdeJWhQ, MjK jLeY Hjf GdfXQjI hGdJWHjb(B. (3aj GdLRA GdChd, jSJYQV GdcJGH GdeHGOF GdCSGSjI dfXQjI GdJShjb GdMOjKI, eY GdJQcjR Ydi CgejI age Sdhc GdeSJgdc hGdJZjQGJ GdeSJeQI aj GdShb(B. (3CeG GdLRA GdKGfj, ajJfGhd LhGfH GdJWHjb GdYedj ddeaGgje GdfXQjI, MjK jbOe CeKdI hGbYjI hcjajI JWHjb COhGJ GdJShjb GdeNJdaI dJMbjb GdCgOGa GdJShjbjI(B. (3jYJHQ gPG GdcJGH eQLkYG bjkeG dcd ef GdHGMKjf hGdeeGQSjf aj eLGd GdJShjb, MjK jRhOge HCMOK GdCacGQ hGdGJLGgGJ aj gPG GdeLGd GdMjhj(B. s
Keywords: (3GdJShjb GdeYGUQs